2010
DOI: 10.1007/s12237-010-9328-8
|View full text |Cite
|
Sign up to set email alerts
|

Can Plant Competition and Diversity Reduce the Growth and Survival of Exotic Phragmites australis Invading a Tidal Marsh?

Abstract: The rapid proliferation of Phragmites australis in North America has challenged resource managers to curb its expansion and reduce the loss of functional tidal marsh. We investigated whether native plant competition could reduce the ability of Phragmites to invade a tidal marsh, and if plant diversity (species richness, evenness, and composition) altered the competitive outcome. Immature Phragmites shoots and four native halophytes were transplanted to small but dense field plots (~1,200 shoots m −2 ) comprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…This has given rise to research to assess feasibility of biological control for the introduced lineage in North America (Tewksbury et al 2002a;Blossey 2003;Häfliger et al 2006a, b;Blossey and Casagrande 2016). Interestingly, there appears to be important biotic resistance to the non-native lineage in less disturbed areas further from human impact (Taddeo and De Blois 2012) and with thriving native plant competitors (Peter and Burdick 2010).…”
Section: Study Speciesmentioning
confidence: 99%
“…This has given rise to research to assess feasibility of biological control for the introduced lineage in North America (Tewksbury et al 2002a;Blossey 2003;Häfliger et al 2006a, b;Blossey and Casagrande 2016). Interestingly, there appears to be important biotic resistance to the non-native lineage in less disturbed areas further from human impact (Taddeo and De Blois 2012) and with thriving native plant competitors (Peter and Burdick 2010).…”
Section: Study Speciesmentioning
confidence: 99%
“…; Frankow‐Lindberg et al . ) and specifically against P. australis (Peter & Burdick ). Field observational studies reported similar patterns at community scale (Levine ; Brown & Peet ), but opposite patterns at larger scale (Stohlgren et al .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have tested the relevance of biotic resistance to the restoration of wetland communities (Wang et al . ; Carlson, Kowalski & Wilcox ; Peter & Burdick ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of biotic resistance to invasions has been widely investigated in freshwater ecosystems. The importance of competition in biotic resistance has been shown for macrophytes, whose growth is reduced with increasing density and diversity of native species (Peter and Burdick, 2010;Michelan et al, 2013). Herbivory also plays a role in reducing invasive macrophytes abundance, as evidenced by the impacts of beavers on one species of invasive macrophyte in wetlands (Parker et al, 2007).…”
Section: Invasibility: Susceptibility Of Aquatic Communities To Invasionmentioning
confidence: 99%